CHALLENGES OF FINANCING THE CURRENT ACCOUNT DEFICIT OF THE REPUBLIC OF SERBIA - Čakajac, Božidar; Janković, Nenad; Dimitrijević, Miloš (The European Journal of Applied Economics, 2024)
One of the central issues related to the presence of a current account deficit is related to finding sources for its financing. Developing countries, including the Republic of Serbia, due to the lack of capital and the disparity between domestic accumulation and investment spending find a solution for financing the current account deficit in the import of foreign capital, which results in financial balance surpluses. In conditions of insufficient inflow of foreign capital, an additional source of financing the balance of payments imbalance is borrowing abroad. The aim of the research is to identify the key sources of financing the current account deficit of the Republic of Serbia in the 2007-2022 period. The research results suggest that, although during the last few years the coverage of the current account deficit is largely provided by the net inflow of foreign direct investments, these funds are still not sufficient to ensure the financing of the deficit components of the current account of the Republic of Serbia. This is greatly contributed by the fact that one of the main deficit components is precisely the ever-increasing outflow of income that is realized on the basis of these investments. Due to all of the above, borrowing abroad is still used as an option for financing the deficit.
Keywords: current account deficit; remittances; foreign direct investments; external debt